Image Of Cholesterol Levels In Obesity Patients In Bulukumba District - Ulil Asmi; Arfiani Nur; Asri (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2020)
Obesity is a condition in which abnormal fat accumulation or excessive adipose tissue so it can be detrimental to health. Diketahuii LDL cholesterol levels in the obese in District ujung loe Bulukumba. Metode district is the method of fully automatic. Principally cholesterol checked after enzymatic hydrolysis and oxidation. Research shows that the results of the LDL-cholesterol levels in 28 obese people showed normal levels of LDL cholesterol as much as 12 samples, high LDL cholesterol levels limit as much as 13 samples, and high cholesterol levels only 3 samples. Of the 28 serum samples obtained from patients with obesity result of normal LDL cholesterol levels as much as 9 samples, high LDL cholesterol levels limit as much as 17 samples, and high cholesterol levels just two samples. For further research should compare the respondent to maintain a diet and exercise regularly. Regular exercise can help you lose excess weight and regulate eating to avoid the various problems due to being overweight include increased levels of LDL in the blood.